ELEMENTE DEFINITORII PRIVIND SPECIFICUL DREPTULUI LA MUNCĂ AL CONDAMNAȚILOR ÎN SISTEMUL PENITENCIAR AL REPUBLICII MOLDOVA - Mazniuc, Diana; Zubco, Alexandru (SUPREMANCE OF LAW, 2019)
In the article, the authors describe the characteristic elements of the right to work carried out by convicts in the penitentiary institutions of the Republic of Moldova. The study includes arguments regarding the need to ensure the right to work in places deprived of liberty, as well as the challenges faced by the prison system in ensuring it. The article contains relevant and real data from the prison system. This article is funded by the European Union (European Instrument for Democracy and Human Rights). Opinions expressed in the article do not necessarily represent those of the European Union.